2022
DOI: 10.1007/s11060-022-04151-z
|View full text |Cite
|
Sign up to set email alerts
|

Moderately hypofractionated versus conventionally fractionated radiation therapy with temozolomide for young and fit patients with glioblastoma: an institutional experience and meta-analysis of literature

Abstract: Purpose Shorter hypofractionated radiation therapy (HF-RT) schedules may have radiobiological, patient convenience and healthcare resource advantages over conventionally fractionated radiation therapy (CF-RT) in glioblastoma (GBM). We report outcomes of young, fit GBM patients treated with HF-RT and CF-RT during the COVID-19 pandemic, and a meta-analysis of HF-RT literature in this patient subgroup. Methods Hospital records of patients with IDH-wildtype GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(60 reference statements)
0
3
0
1
Order By: Relevance
“…In a study by Stupp et. al median PFS was 6.9 months in radiotherapy + TMZ arm and 5 months with radiotherapy alone, with a HR of 0.54, p < 0.001 [4].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a study by Stupp et. al median PFS was 6.9 months in radiotherapy + TMZ arm and 5 months with radiotherapy alone, with a HR of 0.54, p < 0.001 [4].…”
Section: Discussionmentioning
confidence: 97%
“…The landmark Stupp trial showed survival bene t of addition of chemotherapy and formed the basis of post-operative standard of care for HGG patients [4]. However, the protracted long course conventional fractionated radiotherapy regimen HGG is quite inconvenient for patients, taking more than 6 weeks to complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 As a result, different centers adopted different approaches to providing cancer surgery. 19,[21][22][23]…”
Section: Discussionmentioning
confidence: 99%
“…Цій категорії пацієнтів присвячена опублікована у 2022 р. праця P. Chidle та співавт., в якій порівняли результати гіпофракційного (CВД -50,0 Гр, 20 фракцій) та конвенційного (СВД -60,0 Гр, 30 фракцій) режимів ПТ у пацієнтів з ГБ молодого віку з високим рівнем функціонального стану (young and fit patients). Установлено, що гПТ може забезпечити еквівалентні результати лікування та зменшити навантаження від лікувального процесу порівняно зі стандартною ПТ у молодих пацієнтів з ГБ з високим функціональним статусом [22].…”
Section: аналіз співвідношення ризику смерті та прогресування залежно...unclassified